The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/f6041157
|View full text |Cite
|
Sign up to set email alerts
|

If Long-Term Resistance to a Spruce Beetle Epidemic is Futile, Can Silvicultural Treatments Increase Resilience in Spruce-Fir Forests in the Central Rocky Mountains?

Abstract: Abstract:Within the Central Rocky Mountains, spruce beetle populations have the potential to rapidly transition from endemic to epidemic levels in the spruce-fir (Engelmann spruce and subalpine fir) forest type. Conventional management has focused on creating resistance to spruce beetle outbreaks by manipulating the overstory density and composition. Three silvicultural treatments, single tree selection, group selection, and shelterwood with reserves, were established in a spruce-fir forest in northern Utah wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Resistance metrics were based on Schmid and Frye's (1977) spruce beetle risk categories and focused on overstory structure and composition. However, Windmuller-Campione and Long (2015) as well as others Long 2012, Hart et al 2014b. ) observed that management, at best, provides only short-term resistance to the spruce beetle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance metrics were based on Schmid and Frye's (1977) spruce beetle risk categories and focused on overstory structure and composition. However, Windmuller-Campione and Long (2015) as well as others Long 2012, Hart et al 2014b. ) observed that management, at best, provides only short-term resistance to the spruce beetle.…”
mentioning
confidence: 99%
“…Because Engelmann spruce regeneration is key to maintaining spruce-fir stands after a spruce beetle epidemic, we define resilience based on a minimum amount of Engelmann spruce regeneration (Windmuller-Campione and Long 2015). Spruce regeneration, trees Ͻ1 in.…”
mentioning
confidence: 99%
“…The annual increase of 0.4% per year corresponds to levels recorded during the peak bark beetles attack year of 2006, following the major storm Gudrun in 2005. Only trees with a diameter at breast height (dBH) larger than 20 cm were exposed to bark beetles damage [47]. The percentage of spruce bark beetle damage in the stand was calculated once every five years.…”
Section: Simulation Of the Risk Of Spruce Bark Beetle Damage Under Cumentioning
confidence: 99%
“…One framework to manage under this uncertainty is to increase forests resilience to disturbance [9][10][11][12][13]. In this study we use the resilience definition: "the capacity of a system to absorb disturbance and reorganize while undergoing change so as to still retain essentially the same function, structure, identity, and feedbacks" [14].…”
Section: Introductionmentioning
confidence: 99%
“…A second aspect of resilience is the degree of impact on forest ecosystems due to expected pests, disease, and drought. Changing the species, structural, and age class composition through management is another way to potentially lower the severity of disturbances thereby increasing resilience (e.g., [12,13,24,25]). Dymond et al [20] identified the potential benefits of greater tree species diversity in increasing socio-ecological resilience through proactive management of an extensive insect outbreak.…”
Section: Introductionmentioning
confidence: 99%